Analyzing the Impacts of Social Media Use on Learning English Language - Ajab Ali Lashari; Yusra Rizvi; Farah Naz Abbasi; Shehla Anwer Kurd; Mushtaque Ahmed Solangi; Mehboob Ali Golo (Al-Qanṭara, 2023)
The study investigates the using social media and it’s impacts on learning English language. Social media has been used widely for connecting with the social world locally and globally, for entertainment purposes and information sharing. Social media platforms offer cost-effective and versatile channels of communication that are accessible to young individuals despite their widespread geographical distribution. The data was collected from a sample of 307 undergraduate learners at SMIU Karachi using the survey approach. The study utilizes a quantitative methodology for both data collection and analysis. SPSS was used for the data analysis. The study's findings suggest that numerous social media platforms have been used as the tools for learning in the context of learning English language. Undergraduate students use social platforms to augment their language speaking abilities, develop language fluency, participate in public speaking, and proficiently convey their perspectives. It is recommended that the use of social media platforms is easy for the facilitation of constructivist learning. This study offers significant insights for stakeholders, including learners, instructors, parents, and researchers, about the application of social media for teaching and learning purpose among young learners.